OVERCOMING CHALLENGES IN THE AIRPORT AUTHORITY OF ANDI JEMMA MASAMBA AIRPORT - Hartono, Hartono; Rismawati, Rismawati; Aqsa, Muhammad (Universitas Islam Lamongan, 2024)
Airport management always poses challenges in its administration. In addition to requiring high-security standards, airport management must provide well-standardized services. This research was conducted to understand how a well-planned airport management development aligns with existing standards. In this study, the author tested the hypothesis regarding the importance of commanding/charismatic leadership in ensuring the implementation of an airport management system that meets service standards. The research was conducted at Andi Jemma Masamba Airport in Sulawesi, and the results showed a strong correlation between commanding/charismatic leadership and the improvement of quality at Andi Jemma Masamba Airport.